(untitled) (Research, Society and Development, 2022)
In the present study we evaluated the effect of spectral control of light on anatomical characteristics of leaves in three cultivars minitomatos. The plants were grown in shaded environments with gray type screens, red type and blue type, plus control treatment without shade. The experimental design was a randomized block, split plot, with four replications, submitted plants in full sun showed higher leaf thickness, stomatal density in adaxial and photo morphogenetic process adaptability to environmental conditions, adjusting the photosynthetic process and production of assimilates. The plants cultivated under colored nets exhibited differences in the thickness of the epidermis, with superiority for the adaxial epidermis in relation to the abaxial epidermis, but also for the palisade and spongy parenchyma. The plants kept under different shading screens showed variations on the number of stomata, showing a characteristic of high plasticity with the modified environment. The cultivars Shani and Sweet Miller responded to the environment with the photoselective meshes, highlighting the gain in relation to the number of stomata in the red screen, which consequently may be associated with greater photosynthetic efficiency and production of photoassimilates.